2018
DOI: 10.4103/1319-2442.235183
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patency of arteriovenous fistula in hemodialysis patients

Abstract: The arteriovenous fistula (AVF) is the vascular access of the first choice for hemodialysis (HD). Studies on patency of AVF and its affecting factors reveal a high risk for access failure. The aim of this study was to assess the primary and secondary AVF patency and their determinant factors. It was a retrospective, descriptive study conducted in the HD facility of the Nephrology Department in Rabta University Hospital. We included AVF created before December 2009 in end-stage renal disease (ESRD) patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Zouaghi et al evaluated 126 AVFs for its patency and its determinant factors, 39.6% were diabetics in that cohort, only 18 (14.3%) had BBT-AVF; diabetes did not come as a risk factor for poor patency. 6 Higher frequency of steal syndrome in diabetics may also be due more elderly (having advance atherosclerosis) and female (having smaller vessel diameter) patients in this cohort. Limited patency in diabetics can be due to advance atherosclerosis and poor vessel remodeling, which is expected in these patients.…”
mentioning
confidence: 78%
“…Zouaghi et al evaluated 126 AVFs for its patency and its determinant factors, 39.6% were diabetics in that cohort, only 18 (14.3%) had BBT-AVF; diabetes did not come as a risk factor for poor patency. 6 Higher frequency of steal syndrome in diabetics may also be due more elderly (having advance atherosclerosis) and female (having smaller vessel diameter) patients in this cohort. Limited patency in diabetics can be due to advance atherosclerosis and poor vessel remodeling, which is expected in these patients.…”
mentioning
confidence: 78%
“…Therefore, the optimal option of hemodialysis vascular access for these patients requires appropriate strategies concerning comorbidities such as frailty, geriatric syndrome, and life expectancy [ 16 ]. The previous studies demonstrated high mortality rates in elderly hemodialysis patients using CVC compared with AVF and AVG [ [11] , [12] , [13] , [17] , [18] , [19] , [20] , [21] ]. Our study's mortality rate was 12.9 per 100 person-year, which was similar to Rivara et al [ 22 ]; this reflected the standard of care in our center.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-related bloodstream infections (BSIs) alone have a reported incidence of 1.1 to 5.5 episodes per 1000 catheter days and are associated with increased morbidity, hospitalization, and death.1 Barriers to increasing arteriovenous fistula (AVF) creation prompt the initiation of this project; Inadequate pre-ESRD care. A nephrologist often sees ESRD patients for the first time immediately before initiating long-term dialysis (29). In these cases, a PTFE graft often is constructed to avoid the 4-to 6-month maturation time required for an AV fistula.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inadequate pre-ESRD care. A nephrologist often sees ESRD patients for the first time immediately before initiating long-term dialysis (29). In these cases, a PTFE graft often is constructed to avoid the 4-to 6-month maturation time required for an AV fistula.…”
Section: Introduction 11 Problem Descriptionmentioning
confidence: 99%